Analysis of blood from Zika virus-infected fetuses: a prospective case series. Issue 5 (May 2017) - Schaub, Bruno; Vouga, Manon; Najioullah, Fatiha; Gueneret, Michèle; Monthieux, Alice; Harte, Caroline; Muller, Françoise; Jolivet, Eugénie; Adenet, Clara; Dreux, Sophie; Leparc-Goffart, Isabelle; Cesaire, Raymond; et al.
Summary: Background: Zika virus has spread through the Americas and the Caribbean since early 2015 and was rapidly declared a Public Health Emergency of International Concern by WHO because of the potential association with fetal anomalies. We analysed fetal and maternal fluids and tissues in fetuses with confirmed Zika virus infection prospectively monitored in Martinique, a French Caribbean island. Methods: Since the beginning of the Zika virus outbreak in Martinique, all pregnant women undergo monthly fetal ultrasound examination surveillance. In this study, we prospectively studied all patients with fetal anomalies and a positive amniotic fluid for Zika virus by RT-PCR. Maternal and fetal blood, urine, amniotic fluid, placenta, and fetal tissues were tested for Zika virus by RT-PCR. Fetal blood was analysed to identify haematological and biological anomalies. Findings: Between Jan 1, 2016, and Nov 10, 2016, we recruited eight cases of Zika virus infection. All but two cases were symptomatic during the first trimester. Fetal anomalies were only detected after 20 weeks' gestation. After an initial positive result, amniocentesis became negative in two cases and fetal blood was transiently Zika virus-positive in six cases. Fetal blood analyses showed a cholestatic pattern, anaemia, and infectious response. Interpretation: Normalisation of amniotic fluid and fetal blood for Zika virus, as well as maternal blood and urine, shows the limitations of the performance of these investigations, due to the possibility of false negative results. Abnormal fetal blood needs to be investigated further to establish prognostic factors of severe Zika virus infections. Funding: None.